Advances in Resist Materials and Processing Technology XXVI 2009
DOI: 10.1117/12.820493
|View full text |Cite
|
Sign up to set email alerts
|

Development of polymers for non-CAR resists for EUV lithography

Abstract: Three strategies for approaching the design and synthesis of non-chemically amplified resists (non-CARs) are presented. These are linear polycarbonates, star polyester-blk-poly(methyl methacrylate) and comb polymers with polysulfone backbones. The linear polycarbonates were designed to cleave when irradiated with 92 eV photons and high T g alicyclic groups were incorporated into the backbone to increase T g and etch resistance. The star block copolymers were designed to have a core that is sensitive to 92 eV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The polymers have been designed to incorporate polycyclic structures with the aim of giving a high glass transition temperature (T g ) and etch resistance. By modifying the structure of the repeat units it was found that the T g could be tuned between about 50-170°C [7]. The structure that was chosen for further lithographic evaluation is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymers have been designed to incorporate polycyclic structures with the aim of giving a high glass transition temperature (T g ) and etch resistance. By modifying the structure of the repeat units it was found that the T g could be tuned between about 50-170°C [7]. The structure that was chosen for further lithographic evaluation is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…For chemically amplified resists (CARs) a number of causes have been attributed, but diffusion of photogenerated acids has been reported to be one of the most significant contributing factors [1][2][3]. Our strategy has been to remove acid diffusion from the equation by investigating non-chemically amplified resists (non-CARs) for 193nm and EUV lithography [4][5][6][7]. The mechanism by which these resists function is through a molecular weight solubility switch, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To increase EUV absorption and reduce outgassing, a-trifluoromethane was substituted in PMMA and 50 nm 1 : 1 line/space patterns were resolved with EUV, with a photospeed 4.0 times higher than in PMMA. To increase sensitivity, glass transition temperature and etch resistance, linear polycarbonates with polysulfone backbones were evaluated and demonstrated initial resolutions of 35-50 nm lines/spaces, with low LER-increased sensitivity compared with PMMA [73]. Poly(1-butene sulfone) has been patterned with EUV photons, and this system has resolved 50 nm half-pitch patterns [74].…”
Section: (Iv) Extreme Ultraviolet Non-chemically Amplified Resist Matmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] An issue with this class of resists has been the poor sensitivity. [34] The next generation of excimer lasers have a more powerful laser source which will provide the capability to deliver significantly larger doses to the resist at current scan speeds.…”
Section: Introductionmentioning
confidence: 99%